Challenges of public procurement in Bangladesh: a case study on Roads and Highways (RHD) - Rahman, Md. Kholilur (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2020.